PHENOTYPIC DETECTION OF Escherichia coli PRODUCING Extended Spectrum Beta Lactamases (ESBLs) IN THE REPRODUCTIVE TRACT BALI COW - Lalu Purnama Tasyakusuma; kholik kholik; maratun janah; alfiana laili dwi agustin; septyana eka rahmawati (Jurnal Biosains Pascasarjana, 2022)
Escherichia coli bacteria that are resistant to β-lactam antibiotics and may be able to produce Extended-spectrum β-lactamase (ESBLs) have been found in the reproductive tract of Bali cattle. Escherichia coli that produce ESBL will cause antimicrobial resistance (AMR) which has become a global health problem. The purpose of this study was to detect phenotypically the presence of Escherichia coli that produces ESBL from the reproductive tract of Bali cattle. This research was conducted in February 2022 in Lando Village, Terara District, East Lombok Regency using 8 female Bali cattle on smallholder farms. Reproductive fluid samples were collected using a plastic sheet gun which was inserted into the Brain Infusion Heart (BHI) media and incubated at the Public Health and Calibration Laboratory of West Nusa Tenggara Province. The samples were then cultured in EMBA media for the isolation of Escherichia coli. The isolated Escherichia coli were then identified by gram staining and biochemical tests based on Bergey's manual of determinative bacteriology. The identified Escherichia coli were screened using the disc diffusion method using the antibiotics Penicillin G10U, Ceftazidime 30 μg, and Cefotaxime 30 μg followed by a confirmation test using the double disk synergy test (DDST) method. The results of the screening test showed that only 12.5% of Escherichia coli (1 out of 8 samples) were resistant to Penicillin G, but they had not been detected to produce ESBL phenotypically.